Unpacking the “Rules-Based Order” - Ng, Joel (2019)
The “Rules-Based Order” is increasingly being appealed to against the changing regional structures of the Asia-Pacific. However, understanding what each proponent understands, including differing views, about the term is vital for building a firm consensus to move it forward.